Factors Affecting Drugs Stock Void in Karsa Husada Batu Hospital: What and How? - Danny Indrawardhana; Tatong Harijanto; Ferdinandus Stevanus Kakiay (Berkala Kedokteran, 2018)
Abstract: Data of pharmaceutical quality indicator in Karsa Husada Batu Hospital in January-August 2017 showed non-conformance indicator of drug stock void figure with standard. Based on this, in this present study aim to analyze the factors that influence the occurrence of drug stock void. The research used descriptive method. The results of the study indicate that there are five problems causing the occurrence of drug stock void, the coordination between units not yet running, the implementation of the pharmaceutical HIS that has not been operated, the flow of procurement that has not run optimally, the reporting system of drug stock in the unused user unit and the lack of pharmaceutical personnel in the procurement of drug stock. FGD results indicate the need for plan of action. Short-term programs include daily drug stock reporting and analysis of drug procurement flow. Long-term program in the form of pharmaceutical HIS evaluation, data configuration procedure and report into existing pharmaceutical HIS and conduct socialization/training of pharmaceutical HIS that has been configured. Keywords: pharmaceutial service standard, drug stock void, pharmaceutical Hospital Information System (HIS).